Human Embryonic Stem Cell-Derived Mesenchymal Stem Cell Seeding on Calcium Phosphate Cement-Chitosan-RGD Scaffold for Bone Repair - Chen, Wenchuan (Mary Ann Liebert, Inc., 2013)
Calcium phosphate cement (CPC) has in situ-setting ability and excellent osteoconductivity. Human embryonic stem cells (hESCs) are exciting for regenerative medicine due to their strong proliferative ability and multilineage differentiation capability. However, there has been no report on hESC seeding with CPC. The objectives of this study were to obtain hESC-derived mesenchymal stem cells (hESCd-MSCs), and to investigate hESCd-MSC proliferation and osteogenic differentiation on novel CPC with chitosan immobilized with RGD (CPC-chitosan-RGD). RGD was covalently bonded with chitosan, which was then incorporated into CPC. The CPC-chitosan-RGD scaffold had higher strength and toughness than CPC-chitosan control without RGD (p<0.05). hESCs were cultured to form embryoid bodies (EBs), and the MSCs were then migrated out of the EBs. Flow cytometry indicated that the hESCd-MSCs expressed typical surface antigen profile of MSCs. hESCd-MSCs had good viability when seeded on CPC scaffolds. The percentage of live cells and the cell density were significantly higher on CPC-chitosan-RGD than CPC-chitosan control. Scanning electron microscope examination showed hESCd-MSCs with a healthy spreading morphology adherent to CPC. hESCd-MSCs expressed high levels of osteogenic markers, including alkaline phosphatase, osteocalcin, collagen I, and Runx2. The mineral synthesis by the hESCd-MSCs on the CPC-chitosan-RGD scaffold was twice that for CPC-chitosan control. In conclusion, hESCs were successfully seeded on CPC scaffolds for bone tissue engineering. The hESCd-MSCs had good viability and osteogenic differentiation on the novel CPC-chitosan-RGD scaffold. RGD incorporation improved the strength and toughness of CPC, and greatly enhanced the hESCd-MSC attachment, proliferation, and bone mineral synthesis. Therefore, the hESCd-MSC-seeded CPC-chitosan-RGD construct is promising to improve bone regeneration in orthopedic and craniofacial applications.